Assessing International Sport Federations' Sustainability Practices: Toward Integrating Sustainability in Their Main Sports Events - Moon, Philjoo; Bayle, Emmanuel; François, Aurélien (Frontiers in Sports and Active Living, 2022)
Research question: Sustainability has become a pressing issue for a wide range of organizations, including sports’ world governing bodies. This paper examines (1) how sustainability can be defined in the context of international sport federations and (2) how international federations implement social and environmental sustainability practices. We used an eight-dimensional analytical framework to analyze multiple case studies and drew on neo-institutional theory to interpret the recent changes international federations have made with regard to sustainability. Research methods: Our methodology combined a multiple case study with analyses of official documents and in-depth semi-structured interviews. Results and findings: Our six case studies revealed five approaches to sustainability: (a) implementing sustainability pilot events; (b) partnering with NGOs; (c) partnering with sustainability consultancies; (d) creating a sustainability committee; and (e) launching a comprehensive sustainability strategy with at least a full-time sustainability manager. Implications: In terms of theory, examining our data through the lens of neo-institutional theory provides insights into international federations’ recent sustainability behaviors. Our findings enabled us to draw up a “sustainability ladder” of sport federations’ responsibilities, which can be used to assess the degree to which they have embraced sustainability. In practical terms, our findings should encourage more sport federations to take concrete steps to improve their sustainability by implementing the five approaches.